Electrical Generation and Deletion of Magnetic Skyrmion‐Bubbles via Vertical Current Injection. Issue 45 (27th September 2021) - Yang, Seungmo; Moon, Kyoung‐Woong; Ju, Tae‐Seong; Kim, Changsoo; Kim, Hyun‐Joong; Kim, Juran; Tran, Bao Xuan; Hong, Jung‐Il; Hwang, Chanyong
Abstract: The magnetic skyrmion is a topologically protected spin texture that has attracted much attention as a promising information carrier because of its distinct features of suitability for high‐density storage, low power consumption, and stability. One of the skyrmion devices proposed so far is the skyrmion racetrack memory, which is the skyrmion version of the domain‐wall racetrack memory. For application in devices, skyrmion racetrack memory requires electrical generation, deletion, and displacement of isolated skyrmions. Despite the progress in experimental demonstrations of skyrmion generation, deletion, and displacement, these three operations have yet to be realized in one device. Here, a route for generating and deleting isolated skyrmion‐bubbles through vertical current injection with an explanation of its microscopic origin is presented. By combining the proposed skyrmion‐bubble generation/deletion method with the spin–orbit‐torque‐driven skyrmion shift, a proof‐of‐concept experimental demonstration of the skyrmion racetrack memory operation in a three‐terminal device structure is provided. Abstract : A new route to generate and delete magnetic skyrmion‐bubbles electrically is presented using a vertical current path. The vertical current path concept is easy to integrate with a widely used spin–orbit torque device. Using the vertical current path with a spin–orbit‐torque device, core operations for a skyrmion racetrack memory device in a three‐terminal device are demonstrated.